Looping strategies. Moral slippages between the certain and the uncertain in a Roman temporary housing area - Mario Marasco (lo Squaderno, 2024)
The paper is focused on Bastogi, a housing complex which started as temporary housing for university students and travellers but that become a permanent reality for many individuals experiencing severe housing deprivation. It is highlighted the looping effect, in referring to how classifications such as “squatter” and “people in housing emergency” shape individuals’ perceptions of themselves, or how they can also perpetuate the victim-blaming ideology. The temporary housing assistance policies in Rome have chronicled housing precariousness for a significant portion of the urban population, and a place like Bastogi is a product of these urban policies. Like a heterotopia of marginality, Bastogi is a ‘counter-space’, whose existence denounces the segregating logics that created it. The paper also describes the constant struggle of some people in housing crisis to distance themselves from the imposed labels, and how they navigate this social, moral, and political distance from institutions and the rest of the city.